Beyond rhetoric: debunking myths and misinformation on India’s Project Cheetah - Muliya, Sanath K.; Mathur, Vaibhav C.; Singh, Hemant; Kumar, Abhishek; Kumar, Sanjayan; Bhardwaj, Gobind S. (Frontiers in Conservation Science, 2025)
India’s Project Cheetah, initiated in 2022, represents a holistic wildlife conservation initiative aimed at restoring cheetah populations, reviving grassland ecosystems, and fostering socio-economic benefits in the region. Despite its strong ecological foundation and adherence to IUCN protocols, the project has faced persistent criticism, often rooted in ideological biases, oversimplified extrapolations, and sensationalized narratives. Critics have misrepresented key aspects, such as the use of soft-release bomas, ethical concerns, and veterinary interventions, while ignoring the project’s adaptive management strategies and measurable progress, including its current status. This perspective piece counters misinformation with factual evidence, highlights the project’s scientific and conservation merits, and underscores India’s commitment to harmonizing ecological restoration with developmental progress.